PENGARUH MOTIVASI BELAJAR DAN KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS TERPADU DI SMP NEGERI 15 GORONTALO - Putri Sugiarti Syahrain; Frahmawati Bumulo; Abdulrahim Maruwae; Meyko Panigoro; Agil Bahsoan (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
This study aims to examine the effect of learning motivation and learning independence on students’ learning outcomes in Integrated Social Studies at SMP Negeri 15 Gorontalo, Gorontalo City. This research employed a quantitative approach with a causal associative research design. The population of this study consisted of all students of SMP Negeri 15 Gorontalo, with a sample of 55 students selected using a specific sampling technique. Data were collected through the distribution of questionnaires to measure students’ learning motivation and learning independence, as well as documentation of learning outcomes. Data analysis was conducted using multiple linear regression to determine the effect of the independent variables on the dependent variable. The results indicate that, partially, learning motivation and learning independence have a positive and significant effect on students’ learning outcomes in Integrated Social Studies. Simultaneously, learning motivation and learning independence also have a significant effect on students’ Social Studies learning outcomes. Based on the results of the multiple linear regression analysis, the adjusted R² value was 0.389 or 38.9%, indicating that 38.9% of the variation in students’ learning outcomes can be explained by learning motivation and learning independence, while the remaining 61.1% is influenced by other variables not examined in this study.